2014
DOI: 10.1111/ans.12541
|View full text |Cite
|
Sign up to set email alerts
|

To infiltrate or not? Acute effects of local anaesthetic in breast surgery

Abstract: LA infiltration during breast surgery has a marked opioid sparing effect, which has significant patient benefits as well as reducing nursing workload and drug costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…The surgical procedures performed in the reviewed trials included lumpectomy or mastectomy in 14 of 19 trials [ 10 23 ], with additional Sentinel Lymph Node Biopsy (SLNB) or Axillary Lymph Node Dissection (ALND) [ 10 , 12 , 14 18 , 20 , 21 , 23 ]. Three trials included patients undergoing breast augmentation [ 24 26 ], and two trials also included patients undergoing breast reduction [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The surgical procedures performed in the reviewed trials included lumpectomy or mastectomy in 14 of 19 trials [ 10 23 ], with additional Sentinel Lymph Node Biopsy (SLNB) or Axillary Lymph Node Dissection (ALND) [ 10 , 12 , 14 18 , 20 , 21 , 23 ]. Three trials included patients undergoing breast augmentation [ 24 26 ], and two trials also included patients undergoing breast reduction [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Patients underwent mastectomy, while lumpectomy was performed in 4 studies ( Campbell et al , [ 10 ] ; Cros et al , [ 12 ] ; Gürkan et al , [ 14 ] ; Versyck et al , [ 20 ]). Lanier et al [ 16 ] and Wang et al [ 21 ] reported immediate tissue expander or implant based breast reconstruction.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations